A two-dimensional model for the potential distribution and threshold voltage of short-channel double-gate metal-oxide-semiconductor field-effect transistors with a vertical Gaussian-like doping profile - Dubey S.; Tiwari P.K.; Jit S. (My University, 2025)
A two-dimensional (2D) model for the threshold voltage of the short-channel double-gate (DG) metal-oxide-semiconductor field-effect transistors (MOSFETs) with a vertical Gaussian-like doping profile is proposed in this paper. The evanescent mode analysis has been used to solve the 2D Poisson's equation to obtain the channel potential function of the device. The minimum surface potential has been used to model the threshold voltage of the DG MOSFETs. Threshold voltage variations against channel length for different device parameters have been demonstrated. The validity of the proposed model is shown by comparing the results with the numerical simulation data obtained by using the commercially available ATLAS™, a 2D device simulator from SILVACO. © 2010 American Institute of Physics.